The Cutting-Edge Hadoop Distributed File System: Un-leashing Optimal Performance - Gupta, Anish; Santhiya, P.; Thiyagarajan, C.; Gupta, Anurag; Gupta, Manish; Dwivedi, Rajendra Kr (EAI endorsed transactions on scalable information systems, 2025)
Despite the widespread adoption of 1000-node Hadoop clusters by the end of 2022, Hadoop implementation still encounters various challenges. As a vital software paradigm for managing big data, Hadoop relies on the Hadoop Distributed File System (HDFS), a distributed file system designed to handle data replication for fault tolerance. This technique involves duplicating data across multiple DataNodes (DN) to ensure data reliability and availability. While data replication is effective, it suffers from inefficiencies due to its reliance on a single-pipelined paradigm, leading to time wastage. To tackle this limitation and optimize HDFS performance, a novel approach is proposed, utilizing multiple pipelines for data block transfers in-stead of a single pipeline. Additionally, the proposed approach incorporates dynamic reliability evaluation, wherein each DN updates its reliability value after each round and sends this information to the NameNode (NN). The NN then sorts the DN based on their reliability values. When a client requests to upload a data block, the NN responds with a list of high-reliability DN, ensuring high-performance data transfer. This proposed approach has been fully implemented and tested through rigorous experiments. The results reveal significant improvements in HDFS write operations, providing a promising solution to overcome the challenges associated with traditional HDFS implementations. By leveraging multiple pipelines and dynamic reliability assessment, this approach enhances the overall performance and responsiveness of Hadoop's distributed file system.